2018
DOI: 10.1016/j.jri.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Auto-antibodies against the angiotensin II type I receptor in women with uteroplacental acute atherosis and preeclampsia at delivery and several years postpartum

Abstract: Our results confirm that circulating AT-AA are present significantly more often in preeclampsia than in normotensive pregnancy, however without association to acute atherosis. Whether circulating maternal AT-AA or acute atherosis target young women at increased long-term cardiovascular risk warrants further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…Moreover, previous studies have shown that maternal AT1-AA persisted up to 27 months after pregnancy in 17.2% of women with preeclampsia compared to 2.9% in women with normotensive pregnancy [ 49 ]. Recently, a follow up study on circulating AT1-AA levels at five to eight years postpartum was published which showed that AT1-AA was persistently found in women with a history of preeclampsia, which might relate to their future CVD risk [ 50 ].…”
Section: Molecular Factors Resulting From Inadequate Uteroplacental Perfusion Leading To Preeclampsiamentioning
confidence: 99%
“…Moreover, previous studies have shown that maternal AT1-AA persisted up to 27 months after pregnancy in 17.2% of women with preeclampsia compared to 2.9% in women with normotensive pregnancy [ 49 ]. Recently, a follow up study on circulating AT1-AA levels at five to eight years postpartum was published which showed that AT1-AA was persistently found in women with a history of preeclampsia, which might relate to their future CVD risk [ 50 ].…”
Section: Molecular Factors Resulting From Inadequate Uteroplacental Perfusion Leading To Preeclampsiamentioning
confidence: 99%
“…We have postulated a role in acute atherosis for activating antibodies against the angiotensin II type 1 receptor (AA-AT 1 ), after demonstrating a clear association between AA-AT 1 and preeclampsia ( 54 56 ). Based on our cesarean delivery population, we were unable to demonstrate any association between AA-AT 1 and acute atherosis ( 21 ). However, angiotensin II is known to work synergistically with ET-1 ( 57 ), and studying both of these vasoconstrictor systems simultaneously would shed more light on the possible involvement of G-protein cascades in acute atherosis development.…”
Section: Acute Atherosis Etiologymentioning
confidence: 89%
“…A number of studies have now indicated that women with PE produce this novel agonistic autoantibody to the AT1-AA during pregnancy and up to 8 years after delivery. 65,66 One animal model used to examine the role of AT1AA is the AT1-AA chronic excess model where purified AT1-AA is infused into normal pregnant rats. A number of investigators have shown that AT1-AA signaling, via the AT1 receptor, results in a variety of physiological effects, including TNF-a and ROS generation, both of which have been implicated in PE.…”
Section: Models Used To Examine Role Of Agnostic Angiotensin II Type ...mentioning
confidence: 99%